2011
DOI: 10.1515/astro-2017-0289
|View full text |Cite
|
Sign up to set email alerts
|

Some Properties of Galaxy Structures

Abstract: Abstract. We analysed some properties of galaxies structures based on the PF catalog of galaxy structures (Panko & Flin 2006) and the Tully NBG catalog (Tully 1988). At first, we analyzed the orientation of galaxies in the 247 optically selected rich Abell clusters, having at least 100 members. The distribution of the position angles of galaxies as well as of two angles describing spatial orientation of the galaxy planes were tested for isotropy, applying three statistical tests. We found the relation between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In observations, several investigations have reported the detection of alignments between galaxy spins and walls defined as the boundaries of voids. Flin & Godlowski (1986, 1990) discovered that galaxies' spins tend to be aligned with the Local Supercluster plane, which was recently confirmed by Navarro, Abadi & Steinmetz (2004). Trujillo, Carretero & Patiri (2006) used the SDSS and 2dFGRS to show that the rotation axis of spiral galaxies lies preferentially in the plane of these voids.…”
Section: Introductionmentioning
confidence: 84%
“…In observations, several investigations have reported the detection of alignments between galaxy spins and walls defined as the boundaries of voids. Flin & Godlowski (1986, 1990) discovered that galaxies' spins tend to be aligned with the Local Supercluster plane, which was recently confirmed by Navarro, Abadi & Steinmetz (2004). Trujillo, Carretero & Patiri (2006) used the SDSS and 2dFGRS to show that the rotation axis of spiral galaxies lies preferentially in the plane of these voids.…”
Section: Introductionmentioning
confidence: 84%
“…Disc galaxies have also been suggested to feature intrinsic alignments with each other and with the density field of the largescale distribution of matter. Some observations suggest the direction of the angular momenta ("spin") of disc galaxies is correlated with local super-structures (Flin & Godlowski 1986, 1990Navarro et al 2004) but the observational evidence at this point is less clear than for LRGs, with some works reporting null detections (Slosar & White 2009) or contradictory trends (Trujillo et al 2006;Varela et al 2012). In simulations, disc alignments are found to be smaller than for pressure-supported ellipticals, and there is debate as to whether such alignments are radial or tangential around overdensities of the matter field (Chisari et al 2015;Tenneti et al 2016;Kraljic et al 2019).…”
Section: Intrinsic Alignmentsmentioning
confidence: 99%
“…The spins of galaxies are expected to correlate with the anisotropy of nearby structures (e.g., Navarro et al 2004;Ganeshaiah Veena et al 2019;Kraljic et al 2019, but see Krolewski et al 2019). Observationally, the orientations of disc galaxies are correlated with the large-scale distribution of their neighbouring galaxies both in the Local Volume (Flin & Godlowski 1986, 1990Navarro et al 2004;Noh & Lee 2006) and in the field (Trujillo et al 2006;Jones et al 2010;Tempel & Libeskind 2013). Additionally, Guo et al (2015) showed that SDSS galaxies in filaments have ≈ 50 per cent more satellites than similar-luminosity galaxies outside of filaments, further emphasizing the impact that the large-scale environment has on satellite populations.…”
Section: Introductionmentioning
confidence: 98%